Storm of the century Hide and creep : Zombie Dearest : Last of the living : Night of the living dead : I am Omega - Perry, Luke, 1965-; Cortese, Dan; D'Abo, Olivia; Teague, Lewis; Roberts, Eric, 1956-; Steiger, Rod, 1925-2002; Oxenberg, Catherine, 1961-; Murray, Robin P.; Harris, Kirk; Rubio, Jack; Chudabaula, Art; Collins, Clifton; et al. ([United States] : Echo Bridge Home Entertainment, 2015)
Hide and Creep : Zombies rise from the dead in a small Alabama town and take on a ragtag team of locals.
Zombie Dearest : While digging up the septic tank, Gus unearths an obedient hard-working zombie..a zombie that will do whatever he wants.
Last of the living : Three slackers must step up to the plate to save the human race from flesh-eating zombies.
Night of the living Dead : In this George A. Romero classic, a brother and sister visit the gravesite of their deceased father...but when darkness falls, zombies attack.
I am omega : The lone survivor of a deadly plague is doomed to eternal battle with the mutant creatures that now control the Earth.
I am Omega director, Griff Furst (88 min.)
Title from container spine label.
"Emmy-winning mini-series"--Container insert.
"Includes 7 bonus movies"--Container insert.
Some bonus movies in widescreen format.
Storm of the century originally broadcast on ABC as a mini-series in 1999.
Storm of the century: Tim Daly, Colm Feore, Debrah Farentino, Casey Siemaszko, Jeffrey De Munn.
Keywords: Murder; Serial murderers; Good and evil; College students; High school students; Mentally ill; Shipwrecks -- Bermuda Triangle; Made-for-TV movies; Horror films; Fiction films; Feature films; Film adaptations; Horror television programs; Thrillers (Motion pictures); Slasher films; Television mini-series.; Drama